2021
DOI: 10.18502/jfrh.v15i2.6452
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Nifedipine Alone and the Combination of Nifedipine and Sildenafil in Delaying Preterm Labor: A Randomized Clinical Trial

Abstract: Objective: Recently, sildenafil as a drug effective in relaxing smooth muscles can be used as an adjunct to delay the onset of uterine contractions and therefore the occurrence of preterm labor. The aim of this study was to evaluate the effect of nifedipine combination with sildenafil on preterm delivery compared with nifedipine alone. Materials and methods: This randomized double-blinded clinical trial was performed on pregnant women with a gestational age of 26-34 weeks with singleton pregnancy and sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
4
3
Order By: Relevance
“…In the current study, 40% of the participants in group A had history of preterm birth, whereas; it was 75% in group B. In Elham Mohammadi et al 13 the history of preterm birth was 9.1% in the nifedipine group while it was 21.2% in combination group which was less as compared to our study.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In the current study, 40% of the participants in group A had history of preterm birth, whereas; it was 75% in group B. In Elham Mohammadi et al 13 the history of preterm birth was 9.1% in the nifedipine group while it was 21.2% in combination group which was less as compared to our study.…”
Section: Discussioncontrasting
confidence: 78%
“…In the current study, the birth weight was 2090±372.64 in group A and was 2381.67±492.44 grams in group B. Elham Mohammadi et al 13 conducted a randomized study on 139 women in which 1609.0±204.3 and 2154.5±221.3 (grams) were the mean birth weight identified in the nifedipine and combination group which was a decreased mean birth weight compared to our study.…”
Section: Discussioncontrasting
confidence: 49%
“…On the other hand, there is limited clinical knowledge on the effect of sildenafil in pregnancy [ 3 ]. One study suggests that sildenafil-nifedipine combination may be beneficial in preterm birth [ 4 ]. PDE-5 is the main enzyme responsible for the degradation of cyclic guanosine monophosphate (cGMP) following the release of nitric oxide (NO) from nitrergic nerves or vascular endothelial cells, leading to smooth muscle relaxation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, combining Ca-channel blockers and beta-adrenergic receptor agonists are associated with pulmonary hypertension [ 11 ]. Some evidence exists for synergistic effects with sildenafil and nifedipine [ 4 ]. Additionally, we have previously demonstrated in the pregnant rat, that synergistic tocolytic effects are found when combining terbutaline and magnesium sulfate or terbutaline and nifedipine [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…One clinical trial investigating sildenafil as an add-on therapy to nifedipine, a calcium-antagonist, for threatened preterm labor was retracted due to concerns about the validity of the data [ 46 ]. An Iranian study conducted in 2020 suggested a beneficial effect of adding sildenafil to nifedipine therapy for threatened preterm labor reporting prolonged latency (16 days instead of 10 days), as well as the reduced prevalence of neonatal respiratory distress syndrome (7.6% vs. 25.8%) and higher birth weights (2154 g vs. 1609 g) [ 47 ] ( Table 2 ).…”
Section: Preterm Labormentioning
confidence: 99%